(untitled) (Research, Society and Development, 2024)
Most anticholinergic medications act through muscarinic receptors in the central nervous system, which can lead to a range of adverse effects, including neurodegenerative diseases such as dementia. This study aims to map the evidence available in the literature about the relationship between use of anticholinergics and development of Alzheimer’s Disease. To this end, a scoping review was carried out following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist. The searches were conducted in Biblioteca Virtual em Saúde (BVS), PubMed, Biblioteca Brasileira de Teses e Dissertações and ScienceDirect databases, considering only studies carried out in humans, without restrictions on publication date, geographic location or publisher. Editorial articles, correspondence, book chapters, book reviews, encyclopedias, errata, exams, mini reviews, news, short communications and conference abstracts were excluded. The selected studies were organized using Rayyan software, 68 articles were considered eligible for full reading and 13 were included in the final analysis. Among these, 4 studies didn’t find an association between the use of anticholinergics and development of Alzheimer’s disease. However, 9 studies reported a significant correlation between long-term use of anticholinergics and cognitive deterioration, suggesting an increased risk of developing dementia, including Alzheimer’s disease. Therefore, evidence indicates a consistent association between long-term use of anticholinergic medications and increased risk of neurodegenerative diseases.